Development of a Website-Based Complementary Therapy “Interdialysis Symptom Management” for End-Stage Renal Disease Patients - Erika Nurwidiyanti; Maryudella Afrida (Universitas Jenderal Achmad Yani Yogyakarta, 2025)
Background: Interdialytic weight gain (IDWG) is common in patients with end-stage renal disease (ESRD) undergoing hemodialysis. IDWG should not exceed 4.8% of the patient's dry body weight, or approximately 1.5–2.0 kg. Excessive IDWG can increase morbidity and mortality. Website-based complementary therapies can help patients manage their interdialysis symptoms at any time and on their own.Objective: To design and determine the validity of the website-based complementary therapy education media “Interdialysis Symptom Management” for ESRD patients.Methods: This research used the ADDIE (Analysis, Design, Development, Implementation, Evaluation) approach. This website-based educational media contains five menus: Home, PGTA, IDWG, Complementary Therapy, and Patient Journal. Data were collected through interviews, questionnaires, and expert validation (material, language, and media experts). The study was also piloted on 15 hemodialysis patients at PKU Muhammadiyah Yogyakarta General Hospital. The data were analysed quantitatively.Results: Six experts' content validity results indicated that the media was highly feasible, with CVI scores of 0.92-1.00 (≥0.80). Field tests also revealed that the media was feasible for use, with an average score of 77.75%. The developed media was well received by the patients.Conclusion: Website-based complementary therapy proved to be very feasible and received positive feedback from ESRD patients undergoing hemodialysis.